The correlation of triglyceride/high-density lipoprotein cholesterol ratio with muscle mass in type 2 diabetes patients - Qingsong Fu; Zhenwen Zhang; Wenchao Hu; Yinrong Yang (BMC Endocrine Disorders, 2023)
Abstract Objective Triglyceride/high-density lipoprotein cholesterol (TG/HDL-C) ratio is correlated with metabolic diseases. The prevalence of sarcopenia is significantly higher in type 2 diabetes mellitus (T2DM) patients compared with healthy controls. The purpose of our study is to evaluate the correlation of TG/HDL-C ratio with muscle mass in T2DM patients. Method Our study consists of 1048 T2DM inpatients recruited from the department of endocrinology. Skeletal muscle index (SMI) was detected with a dual energy X-ray absorptiometry method. Low muscle mass was diagnosed using the criteria of SMI less than 7.0 kg/m2 (in male subjects) or 5.4 kg/m2 (in female subjects). Result The prevalence of low muscle mass was 20.9% and 14.5% in male and female groups respectively. SMI was correlated with TG/HDL ratio after adjustment for age, duration of diabetes, diastolic blood pressure (DBP), and HbA1c in male subgroup. In female subgroup, SMI was associated with TG/HDL ratio after adjustment for age and DBP. Conclusion Higher TG/HDL-C ratio is correlated with muscle mass in T2DM patients.